Method for preparing aluminum-titanium alloy from ionic liquid in atmospheric environment at room temperature
The method of preparing aluminum-titanium alloys through an ionic liquid room temperature and atmospheric environment has solved the problem of poor quality of aluminum-titanium alloy coating, achieved the improvement of the integrity, uniformity and binding force of the coating, reduced production costs and energy consumption, and is suitable for a variety of matrix materials.
Patent Information
- Application Number
- CN202510497825.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-21
- Publication Date
- 2025-08-15
AI Technical Summary
It is difficult for the prior art to prepare high-quality aluminum-titanium alloy coatings in an open environment. The coating cover is incomplete, the thickness is uneven, and the bonding force with the substrate is weak. The traditional methods require high equipment and high energy consumption.
The aluminum-titanium alloy method is used to prepare ionic liquid at room temperature and atmospheric environment. By strictly controlling the preparation of ionic liquids, precisely building electrode systems, composite atmosphere protection electrode deposition and optimize post-treatment processes, we ensure stable plating quality and performance.
It has achieved complete coverage of aluminum-titanium alloy coating, uniform thickness and strong bonding force with the matrix, reducing equipment requirements and energy consumption, and is suitable for a variety of matrix materials, meeting the performance requirements of different application scenarios.
Smart Images

Figure CN120485896A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aluminum alloy preparation, in particular to a method for preparing aluminum-titanium alloy in an ionic liquid room temperature atmospheric environment. Background Art
[0002] Aluminum, a lightweight metal, forms a dense oxide film on its surface, which promotes corrosion and oxidation resistance. Aluminum coatings offer advantages such as electrical and thermal conductivity, as well as decorative properties, and are widely used in products such as aircraft wings and automobile bodies.
[0003] Aluminum-titanium alloy coatings excel in corrosion resistance, oxidation resistance, and thermal stability, and are widely used in energy, automotive, aerospace, and other fields. Currently, the electrolytes for the electrodeposition of aluminum-titanium alloys on metal substrates mainly include high-temperature molten salts and chloroaluminate ionic liquids. The high-temperature molten salt system is highly corrosive and has high energy consumption. Ionic liquids have a low melting point, low saturated vapor pressure, high electrical conductivity, and a wide electrochemical window. Aluminum chloride and titanium tetrachloride are often used as aluminum and titanium sources, respectively, for the electrodeposition of Al-Ti alloys. However, titanium chloride, as a titanium source, requires a closed operating environment with extremely low water and oxygen values, which is extremely unsuitable for industrial production. Potassium fluorotitanate, as one of the raw materials for the industrial preparation of metallic titanium, has stable chemical properties at room temperature and good solubility in ionic liquid systems. Compared with titanium tetrachloride, its operating conditions are more relaxed and its application prospects are broader.
[0004] In addition, when preparing aluminum-titanium alloy coatings, traditional methods have difficulty ensuring coating quality, often resulting in incomplete coating coverage and uneven thickness, and weak bonding between the coating and the substrate, resulting in unstable product performance. In this context, a new preparation method is urgently needed to overcome the above-mentioned shortcomings and achieve efficient, low-cost, and high-quality preparation of aluminum-titanium alloys. The method of preparing aluminum-titanium alloys in an ionic liquid room temperature atmospheric environment has emerged. Summary of the Invention
[0005] (1) Technical problems solved
[0006] In response to the shortcomings of the existing technology, the present invention provides a method for preparing aluminum-titanium alloy in an ionic liquid room temperature atmospheric environment, which has the advantages of excellent aluminum-titanium alloy coating quality, stable performance, low equipment requirements, and high practicality, solving the problem of poor aluminum-titanium alloy coating quality.
[0007] (2) Technical solution
[0008] In order to achieve the above-mentioned purpose of excellent quality of aluminum-titanium alloy coating, stable performance, low equipment requirements and high practicality, the present invention provides the following technical solution: a method for preparing aluminum-titanium alloy in an ionic liquid room temperature atmospheric environment, comprising the following steps:
[0009] S1. Preparation of ionic liquid electrolyte
[0010] In a closed reaction vessel, an inert nitrogen atmosphere must be created first. This is because during the preparation of the entire ionic liquid, it is necessary to avoid impurities such as oxygen and moisture in the air from adversely affecting the reaction. Nitrogen has stable chemical properties and can provide a pure environment for the reaction. During the specific operation, the air in the container can be replaced by continuously introducing high-purity nitrogen into the reaction vessel for a period of time. Then, the organic compound and anhydrous aluminum chloride are mixed in a specific molar ratio to prepare the ionic liquid. The organic compound can be selected from common organic salts such as 1-butyl-3-methylimidazolium chloride, and anhydrous aluminum chloride is the key component for the formation of ionic liquids. The molar ratio is controlled between 1:1.3 and 2.5. This is the appropriate range verified by a large number of experiments. If the proportion of anhydrous aluminum chloride is too low, it may not be formed. To form a stable ionic liquid structure; if the ratio is too high, it may cause side reactions in subsequent reactions or affect the performance of the ionic liquid. After the two are fully mixed to form an ionic liquid, an inorganic compound of titanium, such as titanium tetrachloride, titanium oxysulfate, etc., is added thereto. After addition, a stirring device, such as a magnetic stirrer, is required to stir at an appropriate speed (such as 300-500 rpm) so that the inorganic compound of titanium can be evenly dispersed in the ionic liquid, thereby forming an ionic liquid electrolyte, and the concentration of the inorganic compound of titanium in the ionic liquid electrolyte must be strictly controlled within the range of 0.11 to 0.45 mol / L. If the concentration is too low, the titanium content in the finally prepared aluminum-titanium alloy may be insufficient, and the expected performance requirements may not be achieved; if the concentration is too high, uneven titanium deposition may be caused, affecting the quality of the alloy;
[0011] S2. Precision construction of electrode system
[0012] A DC power supply is used for electrodeposition to construct a dual-electrode system. The anode is a metal sheet, and usually a high-purity aluminum sheet can be selected because the aluminum sheet can stably provide aluminum ions during the electrodeposition process and participate in the formation of the alloy. The cathode is the substrate. The choice of the substrate should be determined according to the actual application requirements. For example, it can be a stainless steel sheet, a copper sheet, etc. When building the electrode system, the distance between the cathode and the anode needs to be accurately set, and the distance is controlled at 0.15-0.25cm. This is to ensure uniform electric field distribution so that the electrodeposition process can be carried out stably and efficiently. If the distance is too small, the current density between the two electrodes may be too large, resulting in local overheating and other problems, affecting the deposition quality of the alloy; if the distance is too large, the electric field strength will be weakened, resulting in a slower electrodeposition rate and even uneven deposition.
[0013] S3, composite atmosphere protection electrodeposition
[0014] An oily liquid is injected into the electrolytic cell. The oily liquid can be a liquid with chemical stability and good insulation performance, such as silicone oil. The purpose of injecting the oily liquid is to completely cover the ionic liquid electrolyte prepared in step 1, forming a protective film to further isolate the oxygen and moisture in the air to prevent them from interfering with the electrodeposition process. Subsequently, a mixture of hydrogen and nitrogen is introduced into the ionic liquid electrolyte. The mixing ratio of hydrogen and nitrogen can be adjusted according to actual conditions. For example, the volume ratio of hydrogen to nitrogen can be 1:3. The distance between the gas pipe and the cathode should be controlled at 0.15-0.25 cm. This ensures that the mixed gas can evenly enter the electrolyte and form a suitable reaction atmosphere near the cathode. Hydrogen is used in the electrodeposition process. It can play a reducing role, promote the reduction and deposition of titanium ions, and also help to improve the microstructure of the alloy. After the mixed gas is introduced, the electrodeposition operation begins, and the current density is controlled within the range of 5 to 30 mA cm-2. The current density will directly affect the electrodeposition rate and the quality of the alloy. If the current density is too small, the electrodeposition rate will be very slow and the production efficiency will be low; if the current density is too large, it may cause problems such as rough deposited layer and cracks. The electrodeposition process is carried out at room temperature for 0.5 to 4 hours. The length of the deposition time is determined according to the required alloy coating thickness and performance. If the time is too short, the coating thickness may be insufficient; if the time is too long, the coating may be too thick, which wastes resources and may cause other quality problems.
[0015] S4. Post-processing process optimization
[0016] When the electrodeposition is completed, the substrate needs to be taken out in time. When taking out the substrate, it is necessary to operate carefully to avoid damaging the alloy coating that has been deposited on the surface of the substrate. The substrate is then quickly rinsed with anhydrous ethanol. Anhydrous ethanol has good solubility and volatility, and can effectively remove the electrolyte and impurities remaining on the surface of the substrate without corrosive effects on the alloy coating. During the rinsing process, the substrate can be gently shaken in anhydrous ethanol to ensure that all parts can be fully cleaned. After the rinsing is completed, the substrate is dried by nitrogen. High-purity nitrogen is used to blow the substrate surface at a certain flow rate (such as 10-20L / min) to make the anhydrous ethanol evaporate quickly, thereby obtaining a dry substrate. After such treatment, the aluminum-titanium alloy coating is successfully prepared.
[0017] S5. Alloy composition detection technology
[0018] In order to accurately understand the quality and performance of the prepared aluminum-titanium alloy coating, it is necessary to conduct composition testing on it. A variety of analytical methods can be used, such as X-ray fluorescence spectrometry (XRF) and energy dispersive spectroscopy (EDS). These methods can quickly and accurately determine the titanium content in the aluminum-titanium alloy coating.
[0019] When conducting component testing, the prepared aluminum-titanium alloy coating sample must first be properly processed, such as grinding and polishing, to ensure the flatness and smoothness of the test surface. Then the sample is placed in the corresponding testing instrument and tested according to the operating instructions of the instrument. The results obtained from the test can be used to determine whether the titanium content in the aluminum-titanium alloy coating meets the expected requirements. If the titanium content does not meet the requirements, the preparation process can be adjusted according to the test results, such as adjusting the concentration of titanium inorganic compounds in the ionic liquid electrolyte, the current density and time of electrodeposition and other parameters to improve the stability and controllability of the preparation process, thereby obtaining an aluminum-titanium alloy coating with excellent performance.
[0020] Preferably, in step S1, 1-ethylpyridine chloride has a low melting point (about 70°C) and good thermal stability, and its pyridine ring structure can react with AlCl4 - It forms a stable coordination system, which is suitable for forming low-viscosity ionic liquids at room temperature. The longer butyl side chain of 1-butylpyridinium chloride can reduce the surface tension of the ionic liquid, improve the wettability of the electrolyte to the substrate, and enhance the system's resistance to hydrolysis. 1-Butyl-3-methylimidazole chloride is a classic imidazole ionic liquid precursor. The weak interaction between anions and cations can form a wide electrochemical window (>4V), which is particularly suitable for metal electrodeposition processes.
[0021] Preferably, in step S1, potassium fluorotitanate (K2TiF6) is used to replace traditional titanium salts to improve solubility. In AlCl3-BMIMCl ionic liquid, the solubility of potassium fluorotitanate can reach 0.65 mol / L (25 ° C), which is much higher than titanium tetrachloride (0.22 mol / L), and can support a higher concentration of titanium ion supply. In addition, fluorotitanate ions (TiF6 2- ) During cathode reduction, fluoride ions can react with aluminum ions to form AlF4 - complex, inhibiting the precipitation of aluminum alone and promoting Al-Ti co-deposition. Potassium fluorotitanate does not contain chlorine, which can avoid Cl - The corrosion to the equipment is small, and the reaction by-product KF can be easily removed by water washing, reducing the difficulty of post-processing.
[0022] Preferably, in step S2, copper, Q235 steel, and stainless steel substrates have different adaptability characteristics, and the copper substrate has excellent electrical conductivity (59.6×10 6S / m) and thermal conductivity (401W / (m·K)), making it suitable for electrodeposition processes that require rapid heat dissipation, especially to avoid local overheating at high current density. Q235 steel substrate: Surface roughness Ra can reach 1.6μm, which is conducive to the mechanical anchoring of the coating. Adhesion tests show that its shear strength can reach 85MPa, making it suitable for surface strengthening of structural parts. The presence of Cr element (18-20%) in the stainless steel substrate causes a dense oxide film to form on its surface. Activation treatment (such as 5% HCl etching) is required before electrodeposition to obtain a uniform Al-Ti coating.
[0023] Preferably, in step S2, aluminum sheet / titanium sheet is used as anode to realize the coordinated supply of dual metal ions. Aluminum sheet anode: provides Al 3+ ions, whose oxidation reaction is Al→Al 3+ +3e - The standard electrode potential is -1.66V (vs SHE), which forms a driving potential difference of 1.2V with the cathode titanium deposition. The titanium sheet anode: Ti→Ti can occur at high current density. 3+ +3e - Reaction (standard potential -1.21V), replenish the titanium ion concentration in the electrolyte, reduce the cathode polarization phenomenon, mixed anode: when the aluminum-titanium sheet is combined at an area ratio of 3:1, the Al in the electrolyte can be 3+ / Ti 3+ The concentration ratio is stabilized at 5:1, and an ideal alloy coating with a Ti content of 15-18% is obtained.
[0024] Preferably, in step S3, when n-decane is used as the covering liquid, n-decane (density 0.73 g / cm 3 ) and ionic liquids (density 1.2-1.4 g / cm 3 ) forms a clear interface, which can effectively inhibit the volatilization loss of electrolyte during the electrodeposition process (evaporation rate <0.05g / (m 2 ·h)), thus having interface stability and mass transfer regulation. The viscosity of n-decane (0.92mPa·s) allows hydrogen bubbles to float smoothly, while suppressing the convection of the electrolyte, so that a stable diffusion layer with a thickness of about 0.2mm is formed near the cathode, which improves safety. The flash point of n-decane is 46°C, which is more flammable than silicone oil (>300°C). However, production safety can be ensured by controlling the liquid level (3-5cm) and nitrogen protection.
[0025] Preferably, in step S3, the volume fraction of hydrogen gas is controlled at 5-20%, and hydrogen reduction occurs, and H2 generates 2H + +2e -→H2↑ reaction, with an overpotential of approximately 0.3-0.5V, can reduce the precipitation potential of titanium, achieve Al-Ti co-deposition, and refine grains. When the H2 content reaches 15%, the cathode current efficiency increases to 82%, the coating grain size is refined from 25nm to 12nm, and the microhardness is increased from HV180 to HV240. Porosity control: Excessive H2 content (>20%) will lead to intensified hydrogen evolution reaction and increase the coating porosity to 3%, while a H2 content of 5% can stabilize the porosity below 0.5%.
[0026] (3) Beneficial effects
[0027] Compared with the prior art, the present invention provides a method for preparing aluminum-titanium alloy in an ionic liquid room temperature atmospheric environment, which has the following beneficial effects:
[0028] 1. The method for preparing aluminum-titanium alloy in an ionic liquid room temperature atmospheric environment ensures the formation of a stable and suitable ionic liquid structure by strictly controlling the molar ratio of organic compounds to anhydrous aluminum chloride and the concentration of titanium inorganic compounds, thereby providing a good foundation for electrodeposition. When constructing the electrode system, the distance between the anode and cathode is precisely set to ensure uniform electric field distribution, making the electrodeposition stable and efficient. During the composite atmosphere protection electrodeposition process, an oily liquid is injected to form a protective film, a hydrogen and nitrogen mixture is introduced, and the current density and deposition time are controlled. These multiple aspects work synergistically to promote the reduction deposition of titanium ions and improve the alloy structure. These measures work together to ensure that the prepared aluminum-titanium alloy coating is of excellent quality and stable performance. In addition, the limitation of the existing technology requiring a closed operating environment with extremely low water and oxygen values is improved. The equipment requirements are low, the practicality is high, and the energy consumption and production costs can be significantly reduced. The prepared aluminum-titanium alloy coating has complete coverage, uniform thickness, and strong bonding with the substrate.
[0029] 2. The method for preparing aluminum-titanium alloy in an ionic liquid room temperature atmospheric environment can accurately control the titanium content in the alloy coating by changing parameters such as the concentration of titanium inorganic compounds in the ionic liquid electrolyte, the current density and time of electrodeposition. For example, in the embodiment, the titanium contents in the aluminum-titanium alloy coatings prepared under different parameter settings are 8.7wt.%, 14.4wt.%, 21.3wt.%, etc., respectively, which can meet the requirements of alloy performance in different application scenarios. At the same time, for different base materials (such as Q235 steel, copper, stainless steel, etc.), good coating adhesion and uniformity are achieved through corresponding pretreatment operations and process adjustments, which provides strong support for the wide application of aluminum-titanium alloys in various fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 is a flow chart of the preparation method of the present invention;
[0031] Figure 2 Schematic diagram of the electrolysis process of the present invention;
[0032] Explanation of the accompanying symbols: 1. DC power supply; 2. Gas pipe for hydrogen and nitrogen mixture; 3. n-decane; 4. Cathode substrate; 5. Anode plate. DETAILED DESCRIPTION
[0033] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0034] Combine Figure 1-Figure 2 A method for preparing aluminum-titanium alloy in an ionic liquid room temperature atmospheric environment comprises the following steps:
[0035] S1. Preparation of ionic liquid electrolyte
[0036] In a closed reaction vessel, an inert nitrogen atmosphere must be created first. This is because during the preparation of the entire ionic liquid, it is necessary to avoid impurities such as oxygen and moisture in the air from adversely affecting the reaction. Nitrogen has stable chemical properties and can provide a pure environment for the reaction. During the specific operation, the air in the container can be replaced by continuously introducing high-purity nitrogen into the reaction vessel for a period of time. Then, the organic compound and anhydrous aluminum chloride are mixed in a specific molar ratio to prepare the ionic liquid. The organic compound can be selected from common organic salts such as 1-butyl-3-methylimidazolium chloride, and anhydrous aluminum chloride is the key component for the formation of ionic liquids. The molar ratio is controlled between 1:1.3 and 2.5. This is the appropriate range verified by a large number of experiments. If the proportion of anhydrous aluminum chloride is too low, it may not be formed. To form a stable ionic liquid structure; if the ratio is too high, it may cause side reactions in subsequent reactions or affect the performance of the ionic liquid. After the two are fully mixed to form an ionic liquid, an inorganic compound of titanium, such as titanium tetrachloride, titanium oxysulfate, etc., is added thereto. After addition, a stirring device, such as a magnetic stirrer, is required to stir at an appropriate speed (such as 300-500 rpm) so that the inorganic compound of titanium can be evenly dispersed in the ionic liquid, thereby forming an ionic liquid electrolyte, and the concentration of the inorganic compound of titanium in the ionic liquid electrolyte must be strictly controlled within the range of 0.11 to 0.45 mol / L. If the concentration is too low, the titanium content in the finally prepared aluminum-titanium alloy may be insufficient, and the expected performance requirements may not be achieved; if the concentration is too high, uneven titanium deposition may be caused, affecting the quality of the alloy;
[0037] S2. Precision construction of electrode system
[0038] A DC power supply is used for electrodeposition to construct a dual-electrode system. The anode is a metal sheet, and usually a high-purity aluminum sheet can be selected because the aluminum sheet can stably provide aluminum ions during the electrodeposition process and participate in the formation of the alloy. The cathode is the substrate. The choice of the substrate should be determined according to the actual application requirements. For example, it can be a stainless steel sheet, a copper sheet, etc. When building the electrode system, the distance between the cathode and the anode needs to be accurately set, and the distance is controlled at 0.15-0.25cm. This is to ensure uniform electric field distribution so that the electrodeposition process can be carried out stably and efficiently. If the distance is too small, the current density between the two electrodes may be too large, resulting in local overheating and other problems, affecting the deposition quality of the alloy; if the distance is too large, the electric field strength will be weakened, resulting in a slower electrodeposition rate and even uneven deposition.
[0039] S3, composite atmosphere protection electrodeposition
[0040] An oily liquid is injected into the electrolytic cell. The oily liquid can be a liquid with chemical stability and good insulation performance, such as silicone oil. The purpose of injecting the oily liquid is to completely cover the ionic liquid electrolyte prepared in step 1, forming a protective film to further isolate the oxygen and moisture in the air to prevent them from interfering with the electrodeposition process. Subsequently, a mixture of hydrogen and nitrogen is introduced into the ionic liquid electrolyte. The mixing ratio of hydrogen and nitrogen can be adjusted according to actual conditions. For example, the volume ratio of hydrogen to nitrogen can be 1:3. The distance between the gas pipe and the cathode should be controlled at 0.15-0.25 cm. This ensures that the mixed gas can evenly enter the electrolyte and form a suitable reaction atmosphere near the cathode. Hydrogen is used in the electrodeposition process. It can play a reducing role, promote the reduction and deposition of titanium ions, and also help to improve the microstructure of the alloy. After the mixed gas is introduced, the electrodeposition operation begins, and the current density is controlled within the range of 5 to 30 mA cm-2. The current density will directly affect the electrodeposition rate and the quality of the alloy. If the current density is too small, the electrodeposition rate will be very slow and the production efficiency will be low; if the current density is too large, it may cause problems such as rough deposited layer and cracks. The electrodeposition process is carried out at room temperature for 0.5 to 4 hours. The length of the deposition time is determined according to the required alloy coating thickness and performance. If the time is too short, the coating thickness may be insufficient; if the time is too long, the coating may be too thick, which wastes resources and may cause other quality problems.
[0041] S4. Post-processing process optimization
[0042] When the electrodeposition is completed, the substrate needs to be taken out in time. When taking out the substrate, it is necessary to operate carefully to avoid damaging the alloy coating that has been deposited on the surface of the substrate. The substrate is then quickly rinsed with anhydrous ethanol. Anhydrous ethanol has good solubility and volatility, and can effectively remove the electrolyte and impurities remaining on the surface of the substrate without corrosive effects on the alloy coating. During the rinsing process, the substrate can be gently shaken in anhydrous ethanol to ensure that all parts can be fully cleaned. After the rinsing is completed, the substrate is dried by nitrogen. High-purity nitrogen is used to blow the substrate surface at a certain flow rate (such as 10-20L / min) to make the anhydrous ethanol evaporate quickly, thereby obtaining a dry substrate. After such treatment, the aluminum-titanium alloy coating is successfully prepared.
[0043] S5. Alloy composition detection technology
[0044] In order to accurately understand the quality and performance of the prepared aluminum-titanium alloy coating, it is necessary to conduct composition testing on it. A variety of analytical methods can be used, such as X-ray fluorescence spectrometry (XRF) and energy dispersive spectroscopy (EDS). These methods can quickly and accurately determine the titanium content in the aluminum-titanium alloy coating.
[0045] When conducting component testing, the prepared aluminum-titanium alloy coating sample must first be properly processed, such as grinding and polishing, to ensure the flatness and smoothness of the test surface. Then the sample is placed in the corresponding testing instrument and tested according to the operating instructions of the instrument. The results obtained from the test can be used to determine whether the titanium content in the aluminum-titanium alloy coating meets the expected requirements. If the titanium content does not meet the requirements, the preparation process can be adjusted according to the test results, such as adjusting the concentration of titanium inorganic compounds in the ionic liquid electrolyte, the current density and time of electrodeposition and other parameters to improve the stability and controllability of the preparation process, thereby obtaining an aluminum-titanium alloy coating with excellent performance.
[0046] Specifically, in step S1, 1-ethylpyridine chloride has a low melting point (about 70°C) and good thermal stability, and its pyridine ring structure can react with AlCl4 - It forms a stable coordination system, which is suitable for forming low-viscosity ionic liquids at room temperature. The longer butyl side chain of 1-butylpyridinium chloride can reduce the surface tension of the ionic liquid, improve the wettability of the electrolyte to the substrate, and enhance the system's resistance to hydrolysis. 1-Butyl-3-methylimidazole chloride is a classic imidazole ionic liquid precursor. The weak interaction between anions and cations can form a wide electrochemical window (>4V), which is particularly suitable for metal electrodeposition processes.
[0047] Specifically, in step S1, potassium fluorotitanate (K2TiF6) is used to replace traditional titanium salts to improve solubility. In AlCl3-BMIMCl ionic liquid, the solubility of potassium fluorotitanate can reach 0.65 mol / L (25 ° C), which is much higher than titanium tetrachloride (0.22 mol / L), and can support a higher concentration of titanium ion supply. In addition, fluorotitanate ions (TiF6 2- ) During cathode reduction, fluoride ions can react with aluminum ions to form AlF4 - complex, inhibiting the precipitation of aluminum alone and promoting Al-Ti co-deposition. Potassium fluorotitanate does not contain chlorine, which can avoid Cl - The corrosion to the equipment is small, and the reaction by-product KF can be easily removed by water washing, reducing the difficulty of post-processing.
[0048] Specifically, in step S2, copper, Q235 steel, and stainless steel substrates have different adaptability characteristics. The copper substrate has excellent electrical conductivity (59.6×10 6 S / m) and thermal conductivity (401W / (m·K)), making it suitable for electrodeposition processes that require rapid heat dissipation, especially to avoid local overheating at high current density. Q235 steel substrate: Surface roughness Ra can reach 1.6μm, which is conducive to the mechanical anchoring of the coating. Adhesion tests show that its shear strength can reach 85MPa, making it suitable for surface strengthening of structural parts. The presence of Cr element (18-20%) in the stainless steel substrate causes a dense oxide film to form on its surface. Activation treatment (such as 5% HCl etching) is required before electrodeposition to obtain a uniform Al-Ti coating.
[0049] Specifically, in step S2, aluminum sheet / titanium sheet is used as anode to realize the coordinated supply of dual metal ions. Aluminum sheet anode: provides Al 3+ ions, whose oxidation reaction is Al→Al 3+ +3e - The standard electrode potential is -1.66V (vs SHE), which forms a driving potential difference of 1.2V with the cathode titanium deposition. The titanium sheet anode: Ti→Ti can occur at high current density. 3+ +3e - Reaction (standard potential -1.21V), replenish the titanium ion concentration in the electrolyte, reduce the cathode polarization phenomenon, mixed anode: when the aluminum-titanium sheet is combined at an area ratio of 3:1, the Al in the electrolyte can be 3+ / Ti 3+ The concentration ratio is stabilized at 5:1, and an ideal alloy coating with a Ti content of 15-18% is obtained.
[0050] Specifically, in step S3, when n-decane is used as the covering liquid, n-decane (density 0.73 g / cm 3 ) and ionic liquids (density 1.2-1.4 g / cm 3) forms a clear interface, which can effectively inhibit the volatilization loss of electrolyte during the electrodeposition process (evaporation rate <0.05g / (m 2 ·h)), thus having interface stability and mass transfer regulation. The viscosity of n-decane (0.92mPa·s) allows hydrogen bubbles to float smoothly, while suppressing the convection of the electrolyte, so that a stable diffusion layer with a thickness of about 0.2mm is formed near the cathode, which improves safety. The flash point of n-decane is 46°C, which is more flammable than silicone oil (>300°C). However, production safety can be ensured by controlling the liquid level (3-5cm) and nitrogen protection.
[0051] Specifically, in step S3, the hydrogen gas volume fraction is controlled at 5-20%, and hydrogen reduction occurs, and H2 generates 2H + +2e - →H2↑ reaction, with an overpotential of approximately 0.3-0.5V, can reduce the precipitation potential of titanium, achieve Al-Ti co-deposition, and refine grains. When the H2 content reaches 15%, the cathode current efficiency increases to 82%, the coating grain size is refined from 25nm to 12nm, and the microhardness is increased from HV180 to HV240. Porosity control: Excessive H2 content (>20%) will lead to intensified hydrogen evolution reaction and increase the coating porosity to 3%, while a H2 content of 5% can stabilize the porosity below 0.5%.
[0052] Example 1
[0053] (1) The ionic liquid is prepared by mixing 1-butyl-3-methylimidazole chloride and anhydrous aluminum trichloride in a molar ratio of 1:1.2 with magnetic stirring. After the two are mixed into a uniform liquid, an inorganic compound of titanium (potassium fluorotitanate) is added, and then stirred for 12 hours to finally form an ionic liquid electrolyte with good fluidity, transparency and uniformity with a concentration of the inorganic compound of titanium (potassium fluorotitanate) of 0.15 mol / L;
[0054] (2) In a two-electrode electrolytic cell, the anode was a titanium sheet, and the cathode was a pretreated substrate (Q235 steel). The distance between the cathode and anode was 0.25 cm. The pretreatment of the substrate (Q235 steel) was as follows: the Q235 steel substrate was first polished with 400-mesh, 800-mesh, 1500-mesh, and 2000-mesh sandpaper, then polished with a polishing cloth and polishing paste, and finally ultrasonically cleaned with anhydrous ethanol and dried with nitrogen.
[0055] (3) A layer of oily liquid (n-decane) was placed over the ionic liquid electrolyte prepared in step 1. A hydrogen and nitrogen mixture was then introduced into the ionic liquid electrolyte, with the distance between the gas pipe and the cathode being 0.25 cm. Electrodeposition was performed at a current density of 20 mA·cm⁻² and room temperature for 0.5 h.
[0056] (4) The power supply is turned off, the ventilation is ended, the substrate is taken out, and the substrate is rinsed with anhydrous ethanol and dried with nitrogen to obtain an aluminum-titanium alloy.
[0057] The composition of the aluminum-titanium alloy coating sample prepared by the method of this embodiment was tested, and the titanium content in the aluminum-titanium alloy coating was 8.7 wt.%.
[0058] Example 2
[0059] (1) The ionic liquid is prepared by mixing 1-butyl-3-methylimidazole chloride and anhydrous aluminum chloride in a molar ratio of 1:2.3 with magnetic stirring. After the two are mixed into a uniform liquid, an inorganic compound of titanium (potassium fluorotitanate) is added, and then stirred for 12 hours to finally form an ionic liquid electrolyte with good fluidity, transparency and uniformity with a concentration of the inorganic compound of titanium (potassium fluorotitanate) of 0.24 mol / L;
[0060] (2) In a two-electrode electrolytic cell, the anode is a titanium sheet, and the cathode is a pretreated substrate (copper). The distance between the cathode and anode is 0.2 cm. The pretreatment of the substrate (copper) is as follows: first, the copper substrate is polished with 400-mesh, 800-mesh, 1500-mesh, and 2000-mesh sandpaper, then polished with a polishing cloth and polishing paste, and finally ultrasonically cleaned with anhydrous ethanol and dried with nitrogen.
[0061] (3) A layer of oily liquid (n-decane) was placed over the ionic liquid electrolyte prepared in step 1. A hydrogen and nitrogen mixture was then introduced into the ionic liquid electrolyte, with the distance between the gas pipe and the cathode being 0.25 cm. Electrodeposition was performed at a current density of 10 mA·cm⁻² and room temperature for 1 h.
[0062] (4) The power supply is turned off, the ventilation is ended, the substrate is taken out, and the substrate is rinsed with anhydrous ethanol and dried with nitrogen to obtain an aluminum-titanium alloy.
[0063] The composition of the aluminum-titanium alloy coating sample prepared by the method of this embodiment was tested, and the titanium content in the aluminum-titanium alloy coating was 14.4 wt.%.
[0064] Example 3
[0065] (1) The ionic liquid is prepared by mixing 1-butyl-3-methylimidazole chloride and anhydrous aluminum trichloride in a molar ratio of 1:1.8 with magnetic stirring. After the two are mixed into a uniform liquid, an inorganic compound of titanium (potassium fluorotitanate) is added, and then stirred for 12 hours to finally form an ionic liquid electrolyte with good fluidity, transparency and uniformity with a concentration of the inorganic compound of titanium (potassium fluorotitanate) of 0.42 mol / L;
[0066] (2) In a two-electrode electrolytic cell, the anode was a titanium sheet, and the cathode was a pretreated substrate (Q235 steel). The distance between the cathode and anode was 0.3 cm. The pretreatment of the substrate (Q235 steel) was as follows: the Q235 steel substrate was first polished with 400-mesh, 800-mesh, 1500-mesh, and 2000-mesh sandpaper, then polished with a polishing cloth and polishing paste, and finally ultrasonically cleaned with anhydrous ethanol and dried with nitrogen.
[0067] (3) A layer of oily liquid (n-decane) was placed over the ionic liquid electrolyte prepared in step 1. A hydrogen and nitrogen mixture was then introduced into the ionic liquid electrolyte, with the distance between the gas pipe and the cathode being 0.2 cm. Electrodeposition was performed at a current density of 15 mA·cm⁻² and room temperature for 3 h.
[0068] (4) The power supply is turned off, the ventilation is ended, the substrate is taken out, and the substrate is rinsed with anhydrous ethanol and dried with nitrogen to obtain an aluminum-titanium alloy.
[0069] The composition of the aluminum-titanium alloy coating sample prepared by the method of this embodiment was tested, and the titanium content in the aluminum-titanium alloy coating was 21.3 wt.%.
[0070] Example 4
[0071] (1) The ionic liquid is prepared by mixing 1-butyl-3-methylimidazole chloride and anhydrous aluminum chloride in a molar ratio of 1:2.1 with magnetic stirring. After the two are mixed into a uniform liquid, an inorganic compound of titanium (potassium fluorotitanate) is added, and then stirred for 12 hours to finally form an ionic liquid electrolyte with good fluidity, transparency and uniformity with a concentration of the inorganic compound of titanium (potassium fluorotitanate) of 0.45 mol / L;
[0072] (2) In a two-electrode electrolytic cell, the anode is a titanium sheet, and the cathode is a pretreated substrate (stainless steel). The distance between the cathode and anode is 0.3 cm. The pretreatment of the substrate (stainless steel) is as follows: first, the stainless steel substrate is polished with 400-mesh, 800-mesh, 1500-mesh, and 2000-mesh sandpaper, then polished with a polishing cloth and polishing paste, then ultrasonically cleaned with anhydrous ethanol and dried with nitrogen.
[0073] (3) A layer of oily liquid (n-decane) was placed over the ionic liquid electrolyte prepared in step 1. A hydrogen and nitrogen mixture was then introduced into the ionic liquid electrolyte, with the distance between the gas pipe and the cathode being 0.2 cm. Electrodeposition was performed at a current density of 10 mA·cm⁻² and room temperature for 3 h.
[0074] (4) The power supply is turned off, the ventilation is ended, the substrate is taken out, and the substrate is rinsed with anhydrous ethanol and dried with nitrogen to obtain an aluminum-titanium alloy.
[0075] The composition of the aluminum-titanium alloy coating sample prepared by the method of this embodiment was tested, and the titanium content in the aluminum-titanium alloy coating was 15.4 wt.%.
[0076] Example 5
[0077] (1) The ionic liquid is prepared by mixing 1-butyl-3-methylimidazole chloride and anhydrous aluminum chloride in a molar ratio of 1:1.8 with magnetic stirring. After the two are mixed into a uniform liquid, an inorganic compound of titanium (potassium fluorotitanate) is added, and then stirred for 12 hours to finally form an ionic liquid electrolyte with good fluidity, transparency and uniformity with a concentration of the inorganic compound of titanium (potassium fluorotitanate) of 0.34 mol / L;
[0078] (2) In a two-electrode electrolytic cell, the anode is a titanium sheet, and the cathode is a pretreated substrate (copper). The distance between the cathode and anode is 0.3 cm. The pretreatment of the substrate (copper) is as follows: first, the copper substrate is polished with 400-mesh, 800-mesh, 1500-mesh, and 2000-mesh sandpaper, then polished with a polishing cloth and polishing paste, and finally ultrasonically cleaned with anhydrous ethanol and dried with nitrogen.
[0079] (3) The ionic liquid electrolyte prepared in step 1 was covered with a layer of oily liquid (n-decane). A hydrogen and nitrogen mixture was then introduced into the ionic liquid electrolyte, with the distance between the gas pipe and the cathode being 0.2 cm. Electrodeposition was performed at a current density of 16 mA·cm⁻² and room temperature for 2 h.
[0080] (4) The power supply is turned off, the ventilation is ended, the substrate is taken out, and the substrate is rinsed with anhydrous ethanol and dried with nitrogen to obtain an aluminum-titanium alloy.
[0081] The composition of the aluminum-titanium alloy coating sample prepared by the method of this embodiment was tested, and the titanium content in the aluminum-titanium alloy coating was 24.4 wt.%.
[0082] Example 6
[0083] (1) The ionic liquid is prepared by mixing 1-butyl-3-methylimidazole chloride and anhydrous aluminum chloride in a molar ratio of 1:2.2 with magnetic stirring. After the two are mixed into a uniform liquid, an inorganic compound of titanium (potassium fluorotitanate) is added, and then stirred for 12 hours to finally form an ionic liquid electrolyte with good fluidity, transparency and uniformity with a concentration of the inorganic compound of titanium (potassium fluorotitanate) of 0.41 mol / L;
[0084] (2) In a two-electrode electrolytic cell, the anode is a titanium sheet, and the cathode is a pretreated substrate (stainless steel). The distance between the cathode and anode is 0.35 cm. The pretreatment of the substrate (stainless steel) is as follows: first, the stainless steel substrate is polished with 400-mesh, 800-mesh, 1500-mesh, and 2000-mesh sandpaper, then polished with a polishing cloth and polishing paste, then ultrasonically cleaned with anhydrous ethanol and dried with nitrogen.
[0085] (3) The ionic liquid electrolyte prepared in step 1 was covered with a layer of oily liquid (n-decane), and a hydrogen and nitrogen mixture was introduced into the ionic liquid electrolyte, with the distance between the gas pipe and the cathode being 0.2 cm. Electrodeposition was carried out at a current density of 20 mA·cm⁻² and room temperature for 4 h.
[0086] (4) The power supply is turned off, the ventilation is ended, the substrate is taken out, and the substrate is rinsed with anhydrous ethanol and dried with nitrogen to obtain an aluminum-titanium alloy.
[0087] The composition of the aluminum-titanium alloy coating sample prepared by the method of this embodiment was tested, and the titanium content in the aluminum-titanium alloy coating was 27.2 wt.%.
[0088] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing aluminum-titanium alloy in an ionic liquid room temperature atmospheric environment, comprising the following steps: S1. Preparation of ionic liquid electrolyte In a closed reaction vessel, an inert nitrogen atmosphere must be created first. This is because during the preparation of the entire ionic liquid, it is necessary to avoid impurities such as oxygen and moisture in the air from adversely affecting the reaction. Nitrogen has stable chemical properties and can provide a pure environment for the reaction. During the specific operation, the air in the container can be replaced by continuously introducing high-purity nitrogen into the reaction vessel for a period of time. Then, the organic compound and anhydrous aluminum chloride are mixed in a specific molar ratio to prepare the ionic liquid. The organic compound can be selected from common organic salts such as 1-butyl-3-methylimidazolium chloride, and anhydrous aluminum chloride is the key component for the formation of ionic liquids. The molar ratio is controlled between 1:1.3 and 2.
5. This is the appropriate range verified by a large number of experiments. If the proportion of anhydrous aluminum chloride is too low, it may not be formed. To form a stable ionic liquid structure; if the ratio is too high, it may cause side reactions in subsequent reactions or affect the performance of the ionic liquid. After the two are fully mixed to form an ionic liquid, an inorganic compound of titanium, such as titanium tetrachloride, titanium oxysulfate, etc., is added thereto. After addition, a stirring device, such as a magnetic stirrer, is required to stir at an appropriate speed (such as 300-500 rpm) so that the inorganic compound of titanium can be evenly dispersed in the ionic liquid, thereby forming an ionic liquid electrolyte, and the concentration of the inorganic compound of titanium in the ionic liquid electrolyte must be strictly controlled within the range of 0.11 to 0.45 mol / L. If the concentration is too low, the titanium content in the finally prepared aluminum-titanium alloy may be insufficient, and the expected performance requirements may not be achieved; if the concentration is too high, uneven titanium deposition may be caused, affecting the quality of the alloy; S2. Precision construction of electrode system A DC power supply is used for electrodeposition to construct a dual-electrode system. The anode is a metal sheet, and usually a high-purity aluminum sheet can be selected because the aluminum sheet can stably provide aluminum ions during the electrodeposition process and participate in the formation of the alloy. The cathode is the substrate. The choice of the substrate should be determined according to the actual application requirements. For example, it can be a stainless steel sheet, a copper sheet, etc. When building the electrode system, the distance between the cathode and the anode needs to be accurately set, and the distance is controlled at 0.15-0.25cm. This is to ensure uniform electric field distribution so that the electrodeposition process can be carried out stably and efficiently. If the distance is too small, the current density between the two electrodes may be too large, resulting in local overheating and other problems, affecting the deposition quality of the alloy; if the distance is too large, the electric field strength will be weakened, resulting in a slower electrodeposition rate and even uneven deposition. S3, composite atmosphere protection electrodeposition An oily liquid is injected into the electrolytic cell. The oily liquid can be a liquid with chemical stability and good insulation performance, such as silicone oil. The purpose of injecting the oily liquid is to completely cover the ionic liquid electrolyte prepared in step 1, forming a protective film to further isolate the oxygen and moisture in the air to prevent them from interfering with the electrodeposition process. Subsequently, a mixture of hydrogen and nitrogen is introduced into the ionic liquid electrolyte. The mixing ratio of hydrogen and nitrogen can be adjusted according to actual conditions. For example, the volume ratio of hydrogen to nitrogen can be 1:
3. The distance between the gas pipe and the cathode should be controlled at 0.15-0.25 cm. This ensures that the mixed gas can evenly enter the electrolyte and form a suitable reaction atmosphere near the cathode. Hydrogen is used in the electrodeposition process. It can play a reducing role, promote the reduction and deposition of titanium ions, and also help to improve the microstructure of the alloy. After the mixed gas is introduced, the electrodeposition operation begins, and the current density is controlled within the range of 5 to 30 mA cm-2. The current density will directly affect the electrodeposition rate and the quality of the alloy. If the current density is too small, the electrodeposition rate will be very slow and the production efficiency will be low; if the current density is too large, it may cause problems such as rough deposited layer and cracks. The electrodeposition process is carried out at room temperature for 0.5 to 4 hours. The length of the deposition time is determined according to the required alloy coating thickness and performance. If the time is too short, the coating thickness may be insufficient; if the time is too long, the coating may be too thick, which wastes resources and may cause other quality problems. S4. Post-processing process optimization When the electrodeposition is completed, the substrate needs to be taken out in time. When taking out the substrate, it is necessary to operate carefully to avoid damaging the alloy coating that has been deposited on the surface of the substrate. The substrate is then quickly rinsed with anhydrous ethanol. Anhydrous ethanol has good solubility and volatility, and can effectively remove the electrolyte and impurities remaining on the surface of the substrate without corrosive effects on the alloy coating. During the rinsing process, the substrate can be gently shaken in anhydrous ethanol to ensure that all parts can be fully cleaned. After the rinsing is completed, the substrate is dried by nitrogen. High-purity nitrogen is used to blow the substrate surface at a certain flow rate (such as 10-20L / min) to make the anhydrous ethanol evaporate quickly, thereby obtaining a dry substrate. After such treatment, the aluminum-titanium alloy coating is successfully prepared. S5. Alloy composition detection technology In order to accurately understand the quality and performance of the prepared aluminum-titanium alloy coating, it is necessary to conduct composition testing on it. A variety of analytical methods can be used, such as X-ray fluorescence spectrometry (XRF) and energy dispersive spectroscopy (EDS). These methods can quickly and accurately determine the titanium content in the aluminum-titanium alloy coating. When conducting component testing, the prepared aluminum-titanium alloy coating sample must first be properly processed, such as grinding and polishing, to ensure the flatness and smoothness of the test surface. Then the sample is placed in the corresponding testing instrument and tested according to the operating instructions of the instrument. The results obtained from the test can be used to determine whether the titanium content in the aluminum-titanium alloy coating meets the expected requirements. If the titanium content does not meet the requirements, the preparation process can be adjusted according to the test results, such as adjusting the concentration of titanium inorganic compounds in the ionic liquid electrolyte, the current density and time of electrodeposition and other parameters to improve the stability and controllability of the preparation process, thereby obtaining an aluminum-titanium alloy coating with excellent performance.
2. The method for preparing aluminum-titanium alloy in an ionic liquid room temperature atmosphere environment according to claim 1, characterized in that: In the step S1, 1-ethylpyridine chloride has a low melting point (about 70°C) and good thermal stability, and its pyridine ring structure can react with AlCl4 - It forms a stable coordination system, which is suitable for forming low-viscosity ionic liquids at room temperature. The longer butyl side chain of 1-butylpyridinium chloride can reduce the surface tension of the ionic liquid, improve the wettability of the electrolyte to the substrate, and enhance the system's resistance to hydrolysis. 1-Butyl-3-methylimidazole chloride is a classic imidazole ionic liquid precursor. The weak interaction between anions and cations can form a wide electrochemical window (>4V), which is particularly suitable for metal electrodeposition processes.
3. The method for preparing aluminum-titanium alloy in an ionic liquid room temperature atmosphere environment according to claim 1, characterized in that: In step S1, potassium fluorotitanate (K2TiF6) is used to replace traditional titanium salts to improve solubility. In AlCl3-BMIMCl ionic liquid, the solubility of potassium fluorotitanate can reach 0.65 mol / L (25°C), which is much higher than titanium tetrachloride (0.22 mol / L), and can support a higher concentration of titanium ion supply. In addition, fluorotitanate ions (TiF6 2- ) During cathode reduction, fluoride ions can react with aluminum ions to form AlF4 - complex, inhibiting the precipitation of aluminum alone and promoting Al-Ti co-deposition. Potassium fluorotitanate does not contain chlorine, which can avoid Cl - The corrosion to the equipment is small, and the reaction by-product KF can be easily removed by water washing, reducing the difficulty of post-processing.
4. The method for preparing aluminum-titanium alloy in an ionic liquid room temperature atmosphere environment according to claim 1, characterized in that: In step S2, copper, Q235 steel, and stainless steel substrates have different adaptability characteristics. The copper substrate has excellent electrical conductivity (59.6×10 6 S / m) and thermal conductivity (401W / (m·K)), making it suitable for electrodeposition processes that require rapid heat dissipation, especially to avoid local overheating at high current density. Q235 steel substrate: Surface roughness Ra can reach 1.6μm, which is conducive to the mechanical anchoring of the coating. Adhesion tests show that its shear strength can reach 85MPa, making it suitable for surface strengthening of structural parts. The presence of Cr element (18-20%) in the stainless steel substrate causes a dense oxide film to form on its surface. Activation treatment (such as 5% HCl etching) is required before electrodeposition to obtain a uniform Al-Ti coating.
5. The method for preparing aluminum-titanium alloy in an ionic liquid room temperature atmosphere environment according to claim 1, characterized in that: In step S2, aluminum sheet / titanium sheet is used as anode to realize the coordinated supply of bimetallic ions. Aluminum sheet anode: provides Al 3+ ions, whose oxidation reaction is Al→Al 3+ +3e - The standard electrode potential is -1.66V (vs SHE), which forms a driving potential difference of 1.2V with the cathode titanium deposition. The titanium sheet anode: Ti→Ti can occur at high current density. 3+ +3e - Reaction (standard potential -1.21V), replenish the titanium ion concentration in the electrolyte, reduce the cathode polarization phenomenon, mixed anode: when the aluminum-titanium sheet is combined at an area ratio of 3:1, the Al in the electrolyte can be 3+ / Ti 3+ The concentration ratio is stabilized at 5:1, and an ideal alloy coating with a Ti content of 15-18% is obtained.
6. The method for preparing aluminum-titanium alloy in an ionic liquid room temperature atmosphere environment according to claim 1, characterized in that: In step S3, when n-decane is used as the covering liquid, n-decane (density 0.73 g / cm 3 ) and ionic liquids (density 1.2-1.4 g / cm 3 ) forms a clear interface, which can effectively inhibit the volatilization loss of electrolyte during the electrodeposition process (evaporation rate <0.05g / (m 2 ·h)), thus having interface stability and mass transfer regulation. The viscosity of n-decane (0.92mPa·s) allows hydrogen bubbles to float smoothly, while suppressing the convection of the electrolyte, so that a stable diffusion layer with a thickness of about 0.2mm is formed near the cathode, which improves safety. The flash point of n-decane is 46°C, which is more flammable than silicone oil (>300°C). However, production safety can be ensured by controlling the liquid level (3-5cm) and nitrogen protection.
7. The method for preparing aluminum-titanium alloy in an ionic liquid room temperature atmosphere environment according to claim 1, characterized in that: In step S3, the hydrogen gas volume fraction is controlled at 5-20%, and hydrogen reduction occurs, and H2 generates 2H + +2e - →H2↑ reaction, with an overpotential of approximately 0.3-0.5V, can reduce the precipitation potential of titanium, achieve Al-Ti co-deposition, and refine grains. When the H2 content reaches 15%, the cathode current efficiency increases to 82%, the coating grain size is refined from 25nm to 12nm, and the microhardness is increased from HV180 to HV240. Porosity control: Excessive H2 content (>20%) will lead to intensified hydrogen evolution reaction and increase the coating porosity to 3%, while a H2 content of 5% can stabilize the porosity below 0.5%.